Building employee resilience through wellbeing in organizations - Tonkin, Karen; Malinen, Sanna; Näswall, Katharina; Kuntz, Joana C. (Human resource development quarterly, 2018)
The resilience of employees has been recently identified as essential to organizational adaptability in uncertain and dynamic business environments. Yet little is known about how the resilience of employees can be developed. The present study investigated the effect of a wellbeing intervention on two forms of individual resilience: employees' stress‐coping ability (personal resilience) and resilient workplace behaviors (employee resilience). All participants (n = 209) completed an online wellbeing and resilience survey, and a subset of 145 participants took part in a workplace wellbeing intervention for a period of one month, followed by a second survey. The results indicated that personal and employee resilience are two related, but distinct, constructs. Further, following the wellbeing intervention, personal resilience remained stable, but small increases were noted in levels of employee resilience and aspects of wellbeing. Theoretical and practical implications of this research to employee resilience development are discussed.